Respuesta :
Answer: -9
Step-by-step explanation: When you're asked to multiply positives and negatives together, the rules are simple.
A positive times a positive is a positive.
A positive times a negative is a negative.
A negative times a positive is a negative.
A negative times a negative times a negative is a positive.
So for the problem you see here, we will use rule 2 which I have highlighted in bold above which states that a positive times a negative is a negative.
So (+3)(-3) = -9
Answer:
It depends on what the problem is. See below.
Step-by-step explanation:
(3) - 3 = 3 - 3 = 0
If you mean an exponent, then maybe it is
[tex] (3)^{-3} = \dfrac{1}{3^3} = \dfrac{1}{27} [/tex]